E-commerce dan bisnis digital: perbedaan, kelebihan, dan pengaruhnya terhadap pola konsumsi masyarakat - AL MASRUROH, BUSHTANUL FAHMIYAH (Maliki Interdisciplinary Journal, 2026)
Developments in the information and communication sector have influenced major changes in economic activity, particularly through the use of e-commerce and digital business. Although these two terms are often used interchangeably, they have distinct characteristics and scopes. This study aims to compare the differences between e-commerce and digital business, examine the advantages of each, and review their impact on changing the way people purchase goods. To do this, the researcher used a literature review method by gathering information from various national journals, scientific books, and related official reports. The results show that e-commerce emphasizes the online buying and selling process, while digital business encompasses changes in various aspects of business using digital technology. The presence of e-commerce and digital business has influenced people's shopping patterns, such as facilitating access, saving time, and changing purchasing preferences. This research is expected to provide benefits in understanding the dynamics of e-commerce and digital business and their impact on society. Keywords: e-commerce, digital business, consumption patterns, digital technology